Correlation of Classroom Teacher Professionalism and Leadership to Student Learning Outcomes - Nuriyani; Kharis Sulaiman Hasri; Agra Dwi Saputra (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study investigates the relationship between classroom teacher leadership as extracurricular coaches, teacher professionalism, and student learning outcomes at SD Islam Cendikia Faiha. The research aims to explore how these factors contribute to students' academic success. Using a quantitative approach, data were collected through observation, documentation, and questionnaires from 15 classroom teachers who also serve as extracurricular coaches. The data were analyzed using product moment multivariate correlation to determine the strength and significance of relationships between variables. Findings reveal a positive correlation between teacher leadership in extracurricular coaching and student learning outcomes, with a correlation coefficient of 0.57. Additionally, teacher professionalism also shows a positive relationship with student learning outcomes, with a correlation coefficient of 0.53. The multiple correlation analysis confirms a significant combined effect of these two independent variables on student learning outcomes (Fcount 7.78 > Ftable 3.89). These results highlight the crucial role of teacher leadership and professionalism in fostering student academic achievement. The study underscores the importance of empowering teachers with leadership skills and professional development opportunities, especially in extracurricular settings, to enhance student learning experiences. Future research could further explore these relationships in broader educational contexts to validate and extend the findings.